2017
DOI: 10.18632/oncotarget.15631
|View full text |Cite
|
Sign up to set email alerts
|

HES1 promotes extracellular matrix protein expression and inhibits proliferation and migration in human trabecular meshwork cells under oxidative stress

Abstract: Glaucoma is the leading cause of irreversible blindness. The most prevalent form of glaucoma is primary open-angle glaucoma (POAG). Oxidative stress is one of the major pathogenic factors of the POAG, and can elicit molecular and functional changes in trabecular meshwork cells, causing increased aqueous humor outflow resistance and elevated intraocular pressure. However, the regulatory mechanisms underlying oxidative stress-induced cell phenotypic changes remain elusive. Herein, we exposed primary human trabec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Our results showed that in goose granulosa cells, treatment with 3-NPA at 5.0 mmol/l down-regulated the mRNA expression of Pcna and p53 , while it up-regulated Caspase 3 mRNA expression. It is plausible that the diminished proliferative and augmented apoptosis caused by the transient oxidative stress induced by 3-NPA may contribute to the inhibition of granulosa cell viability in geese [ 30 ]. The anti-apoptotic protein Bcl-2 inhibits cytochrome c release and Caspase 3 activation and thus functions as an antioxidant to prevent apoptosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that in goose granulosa cells, treatment with 3-NPA at 5.0 mmol/l down-regulated the mRNA expression of Pcna and p53 , while it up-regulated Caspase 3 mRNA expression. It is plausible that the diminished proliferative and augmented apoptosis caused by the transient oxidative stress induced by 3-NPA may contribute to the inhibition of granulosa cell viability in geese [ 30 ]. The anti-apoptotic protein Bcl-2 inhibits cytochrome c release and Caspase 3 activation and thus functions as an antioxidant to prevent apoptosis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the lentivirus-involving experiments, including packaging, concentration, tittering, and injections, were performed in a dedicated Biosafety Level 2 microbiology laboratory, and all the experimental procedures adhered to the health and safety guidelines stated by BIOSAFETY LEVEL 2 LABORATORY PRACTICES from NIH. The packaging of lentivirus was performed as described previously 43 , 44 . Briefly, 293T cells were seeded on the 6-well plates (Corning, Corning, NY, USA) coated by rat tail collagen (Sigma-Aldrich, St. Louis, MO, USA) at a density of 8 × 10 5 cells / well.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were transduced as previously described 43 , 44 . Briefly, the titers of Lenti-IL-10 and Lenti-RFP were equally adjusted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HES1 regulates the development of cells in the nervous and digestive systems by functioning downstream of the Notch signaling pathway (Kageyama, Ohtsuka & Kobayashi, 2007). Xu et al found that HES1 promotes ECM expression and inhibits TMC proliferation and migration under oxidative stress (Xu et al, 2017). More importantly, HES1 short hairpin RNA (shRNA) has been shown to attenuate ECM protein upregulation and functional defects caused by oxidative stress.…”
Section: Survey Methodologymentioning
confidence: 99%